Efeito do jejum sobre o desempenho zootécnico, crescimento e degradação muscular e alterações hepáticas de juvenis de pacu Piaractus mesopotamicus - Menossi, Olívia Cristina Camilo [UNESP] (2014)
The pacu, Piaractus mesopotamicus, is a species with great economic importance in Brazil and many studies on its initial phase have been conducted to enable the intensive culture of this species. Fish undergo fasting periods, both in natural conditions as in the intensive rearing, causing activation of proteolytic systems due to the breakdown of muscle tissue, which implies the reduction of the skeletal striated muscles of the animal, the edible part of fish. In this way, more research is necessary to understand the formation and breakdown of muscle tissue. In this study, juvenile pacu with 20.4 ± 0.7 mm in total length and 90.3 ± 4.1mg of average weight were stocked in 20 tanks of 50 L at a density of 10 fish/L. The fasting periods evaluated were: J4; J8 and J11, corresponding to 4, 8 and 11 days of fasting. After this period, the fish were refed for 20 days with artemia nauplii. The positive control (ART) was fish fed newly hatched artemia nauplii throughout the experimental period. Samples for growth, histological analysis of liver and muscle fibers and gene expression were collected at the end of each period of fasting and at the end of the experiment. Muscle fibers were distributed into the following diameter classes (d = μm): Class 10 = d ≤ 10, Class 20 = 10 <d ≤ 20, Class 30 = 20 <d ≤ 30, Class 40 = 30 <d ≤ 40, and class d 50 => 40. At the end of the fasting period, growth, survival and the frequency of muscle fibers were affected by fasting. The fish in the treatment J11 showed high incidence of muscle fiber atrophy, as revealed by increased frequencies in classes 10 and 20 fibers. Similar pattern was observed in animals kept eight days fasting (J8). The fish of the treatment J4 showed a lower incidence of muscle fiber atrophy and the frequency of fiber classes 10, 20, 30 and 50 was similar to the positive control. The glycogen storage in the liver of fasted animals was decreased as higher was the fasting ...